Athletes` resilience typology: a comparative analysis of individual and team sports - Popovych, I.; Radul, I.; Hoian, I.; Ohnystyi, A.; Doichyk, M.; Burlakova, I. (Journal of Physical Education and Sport, 2022)
The purpose of the empirical study is to develop and substantiate a typology of athletes` resilience, as well as to compare different types of resilience among representatives of individual sports and team sports. Individual sports are represented by athletes from athletics, boxing, and weightlifting (n=312; average age M=26.2), and team sports are represented by representatives from mini-football, football, handball, and volleyball (n=322, average age M=28.1). Research methods: psychodiagnostic methods that used scales to evaluate the content parameters of the researched phenomena in a relevant way; participant observation; k-means cluster analysis; Spearman method correlation analysis (rs); criterion angle-transformation of Fisher`s (f). Results. It is substantiated that athletes` resilience typology is a scientific classification of abstract theoretical complexes (types) that integrate the most essential content parameters, structural and functional characteristics of athletes` resilience. Commitment (rs=.148), Control (rs=.086), Challenge (rs=.076), Hardiness (rs=.115), Emotional Stability (rs=.146), Cheerfulness (rs=.186), and Motivation to Succeed (rs=.202) were determined as the content factors with the strongest connection to Resilience (p<.01; p<.05). Individual and team sports were formed as empirical typologies of athletes` resilience. Individual athletes` resilience was classified into four types: Value-Oriented (VO), Motivational-Oriented (MO), Socially Acceptable (SA), and Emotionally Stable (ES). The following types of team sports athletes` resilience were identified: Motivational-Valued (MV), Control-Pragmatic (CP), Socially Acceptable (SA), and Resilient (RS). The distinctions in content features of athletes` socially acceptable types of resilience in individual and team sports are substantiated. Conclusions. The first hypothesis was confirmed when two types of athlete resilience were developed. The second hypothesis is confirmed since the construction of resilience types is based on the dominating levels of content parameters. The third hypothesis cannot be statistically proven or disproven since the three types of athletes` resilience differ in content parameters and cannot be compared. The Socially Acceptable type was compared, but no significant differences were found (p >= .05). It is recommended that representatives of individual and team sports consider the obtained results and that they be operationalized in athletes` tactical training.